Confocal x‐ray Fluorescence Imaging Facilitates High‐Resolution Elemental Mapping in Fragile Archaeological Bone. (11th May 2016) - Choudhury, S.; Swanston, T.; Varney, T. L.; Cooper, D. M. L.; George, G. N.; Pickering, I. J.; Grimes, V.; Bewer, B.; Coulthard, I.
Abstract : Synchrotron‐based standard X‐ray fluorescence imaging can be a sophisticated tool for mapping distributions of trace elements in archaeological bone; however, thin samples are normally required to achieve high‐spatial‐resolution results. Poorly preserved or fragile archaeological samples can be challenging to measure using this standard technique, since the production of a sufficiently thin section may be difficult. We discuss the implementation of confocal X‐ray fluorescence imaging as a successful strategy for high‐resolution elemental mapping in poorly preserved archaeological bone. The implementation of the confocal method additionally can facilitate localized quantification and speciation of elements, which are also discussed.